1980
DOI: 10.1111/j.1365-2141.1980.tb05905.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Colony Stimulating Activity in Modulating Murine Diffusion Chamber Granulopoiesis

Abstract: We studied the effects of high circulating Colony Stimulating Activity (CSA) levels and irradiation induced marrow hypoplasia in CF1 and C57B1/6J host mice upon granulopoiesis in intraperitoneal diffusion chamber (DC) cultures. Serial endotoxin injections resulted in marked elevation of circulating CSA for the first half of an 8 d culture period, and CSA was shown to diffuse into the chamber environment; yet this manipulation alone did not significantly accelerate DC cell growth. Pre-irradiation of the host mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Intraperitoneal implantation of diffusion chambers (DC) in live murine hosts has provided a useful model for the study of in vivo regulation of granulopoiesis (Benestad, 1970;Quesenberry et al, 1974). Utilizing this technique, two groups of investigators (Rothstein et al, 1971(Rothstein et al, , 1973Sullivan et al, 1980) have shown that alterations in CSA do not adequately explain the fluctuations that occur in DC granulopoiesis after a variety of experimental manipulations. Rothstein et al (1971Rothstein et al ( , 1973 have described a humoral regulator of granulopoiesis in DC, termed diffusible granulocytopoietic stimulator (DGS), which is experimentally distinct from both CSA and neutrophil-releasing factor.…”
Section: Discussionmentioning
confidence: 99%
“…Intraperitoneal implantation of diffusion chambers (DC) in live murine hosts has provided a useful model for the study of in vivo regulation of granulopoiesis (Benestad, 1970;Quesenberry et al, 1974). Utilizing this technique, two groups of investigators (Rothstein et al, 1971(Rothstein et al, , 1973Sullivan et al, 1980) have shown that alterations in CSA do not adequately explain the fluctuations that occur in DC granulopoiesis after a variety of experimental manipulations. Rothstein et al (1971Rothstein et al ( , 1973 have described a humoral regulator of granulopoiesis in DC, termed diffusible granulocytopoietic stimulator (DGS), which is experimentally distinct from both CSA and neutrophil-releasing factor.…”
Section: Discussionmentioning
confidence: 99%
“…1). 3H-LPS prepared in this manner retained potent endotoxic bioactivity as assessed by its ability to coagulate limulus lysate (Mallinckrodt Laboratories, St. Louis, MO), to elevate the plasma concentration of GM-CSF within 4 hr after injection into CF1 mice (30), and to stimulate isolated human monocytes to secrete GM-CSF activity when added to liquid suspension cultures of these cells at 0.5-1.0 lg/ml (18). For these biologic assays, murine (30) and human (31) GM-CSF was quantified by using tissue culture bioassays that we have described previously.…”
mentioning
confidence: 99%